THE ROLE OF INFORMATION TECHNOLOGY, INTERNAL CONTROL SYSTEMS, AND HUMAN RESOURCES COMPETENCE IN IMPROVING THE VALUE ADDED (VAIC) PERFORMANCE OF STATE-OWNED ENTERPRISES IN INDONESIA - Mutiara, Talita; Hardianto, Ade Manggala; Z Zulkarnain, Z Zulkarnain; Novitasari, Yuli (International Journal of Multidisciplinary Research and Literature, 2025)
This research is motivated by the importance of increasing value added in public sector companies in Indonesia, particularly state-owned enterprises (SOEs), through optimizing information technology, improving the effectiveness of internal control systems, and improving human resource competency. The main objective of this study is to analyze the partial and simultaneous effects of these three variables on company value added. This study uses a quantitative approach with secondary data obtained from the annual reports and financial statements of 20 state-owned enterprises (BUMN) for the period 2019–2023, and processed using panel data regression analysis with a Random Effect model. The results show that information technology and human resource competency have a positive and significant effect on value added, while internal control systems have a positive but insignificant effect. Simultaneously, these three variables have a substantial effect on increasing value added, with an Adjusted R² value of 96.35%. This finding confirms that digital transformation and strengthening human resource capacity are key factors in creating added value and increasing the competitiveness of SOEs in the modern era.